The effect of electroconvulsive therapy on subclinical inflammation in bipolar disorders - Şahin, Şengül Kocamer; Yaşamalı, Celal; Özyürek, Muhammet Berkay; Elboğa, Gülçin; Altındağ, Abdurrahman; Elmalı, Enes; Demirbaş, Handan (Journal of Surgery and Medicine, 2019)
Aim: Growing evidence supports the role of inflammation in the etiology of bipolar disorder. Efficacy of electroconvulsive therapy (ECT) in the manic and depressive phases of bipolar disorder is well-known. We aimed to investigate the effect of ECT on the neutrophil/lymphocyte (NLR) and platelet/lymphocyte ratios (PLR), which are newly defined subclinical inflammatory markers in patients with bipolar disorder. Methods: Patients who received ECT due to the diagnosis of bipolar disorder according to DSM-5 in the last two years and the same number of individuals as the control group were included in this case-control study. NLR and PLR were compared between the patient and control groups, and before and after ECT in the patient group. Results: A total of 104 individuals were included in the study. Among included patients with bipolar disorder, 39 were in depressive episode and 13 were in manic episode. 52 healthy individuals were identified as control group. Patients' mean age was 36.0 (13.4) years. There were no significant differences between the groups in terms of age, gender, marital status, and smoking. NLR values were significantly higher in the patient group before and after ECT compared to the control group. No difference was found between PLR ratios. There was no significant difference between the NLR, PLR values before and after ECT in the patient group. Conclusion: This study supports the hypothesis that subclinical inflammation exists in bipolar patients in both manic and depressive phases and it continues after ECT. Large-scale studies are needed to determine the effects of ECT on subclinical inflammation.